2009
DOI: 10.1080/09500340802267159
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast photodissociation assisted by strong non-resonant Stark effect: the ‘straddling’ control pulse

Abstract: Control of the ultrashort photodissociation dynamics of a diatomic molecule on different excitation channels is investigated by Stark shift with a strong and approximately constant electric pulse, that 'straddles' the pump pulse excitation. The scheme implies first the creation of the light-induced potentials (LIP) in the presence of the control field, then the selective crossing to a single excited LIP by the ultrashort pump pulse, and finally the turn-off of the control field. We observe: (1) blue-shifting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…[29][30][31][32] More recently, we have started to explore its use in controlling chemical reactions. 33,34 The results of this work complement and generalize those findings. In Ref.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…[29][30][31][32] More recently, we have started to explore its use in controlling chemical reactions. 33,34 The results of this work complement and generalize those findings. In Ref.…”
Section: Introductionsupporting
confidence: 83%
“…35,36 On the other hand, in Ref. 34, we worked with the same model as in this work but used essentially a͒ Author to whom correspondence should be addressed. Electronic mail: isola@quim.ucm.es.…”
Section: Introductionmentioning
confidence: 99%
“…21 Especially the latter case is interesting because no highly specific wavelength sources are required, and this non-resonant dynamic Stark effect (NRDSE) has already been the target of several studies. [21][22][23][24][25][26][27][28][29][30] There, reaction pathways are reversibly changed and in this way, the NRDSE acts like a photonic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, most works have been done to create the LIAC or LICI in order to control the output of a photochemical process. In particular, there have been several theoretical proposals to control the yield of a photodissociation reaction [110], as well as the branching ratio over possible fragmentation channels [35,107,109,110] and the kinetic energy distribution of the fragments [111]. Although most proposals remain experimentally untested, owing to the difficulty of finding good molecular systems where the strong field interaction is strong enough to generate LIPs, yet not too strong that the ionization is predominant, recent experiments have shown that indeed such control is possible [8][9][10].…”
Section: Introductionmentioning
confidence: 99%